Measurement and modeling of polarized specular neutron reflectivity in large magnetic fields. Issue 4 (9th June 2016) - Maranville, Brian B.; Kirby, Brian J.; Grutter, Alexander J.; Kienzle, Paul A.; Majkrzak, Charles F.; Liu, Yaohua; Dennis, Cindi L.
Abstract : A procedure is described for polarized neutron reflectometry when the Zeeman corrections are significant, which occurs when both the magnetic anisotropy and the applied magnetic field are significant. Calculations and a recommended procedure for an example system are provided. Abstract : The presence of a large applied magnetic field removes the degeneracy of the vacuum energy states for spin‐up and spin‐down neutrons. For polarized neutron reflectometry, this must be included in the reference potential energy of the Schrödinger equation that is used to calculate the expected scattering from a magnetic layered structure. For samples with magnetization that is purely parallel or antiparallel to the applied field which defines the quantization axis, there is no mixing of the spin states (no spin‐flip scattering) and so this additional potential is constant throughout the scattering region. When there is non‐collinear magnetization in the sample, however, there will be significant scattering from one spin state into the other, and the reference potentials will differ between the incoming and outgoing wavefunctions, changing the angle and intensities of the scattering. The theory of the scattering and recommended experimental practices for this type of measurement are presented, as well as an example measurement.